2022
DOI: 10.3390/gels8030156
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning of Wastewater Using Crosslinked Poly(Acrylamide-co-Acrylic Acid) Hydrogels: Analysis of Rotatable Bonds, Binding Energy and Hydrogen Bonding

Abstract: The discharge of untreated wastewater, often contaminated by harmful substances, such as industrially used dyes, can provoke environmental and health risks. Among various techniques, the adsorption of dyes, using three-dimensional (3D) networks consisting of hydrophilic polymers (hydrogels), represents a low-cost, clean, and efficient remediation method. Three industrially used dyes, Methylene Blue, Eosin, and Rose Bengal, were selected as models of pollutants. Poly(acrylamide) (poly(AM)) and poly(acrylamide-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The negative binding affinity indicates that the ligands spontaneously bind to the enzymes without consuming energy. A higher binding affinity, indicated by a more negative value, corresponds to a higher stability of the binding complex (Hamri et al., 2022). From the interaction between the substrate/reuterin and 1,3‐β‐glucan synthase, we found that UDP–glucose had a higher binding affinity than reuterin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative binding affinity indicates that the ligands spontaneously bind to the enzymes without consuming energy. A higher binding affinity, indicated by a more negative value, corresponds to a higher stability of the binding complex (Hamri et al., 2022). From the interaction between the substrate/reuterin and 1,3‐β‐glucan synthase, we found that UDP–glucose had a higher binding affinity than reuterin.…”
Section: Resultsmentioning
confidence: 99%
“…A rotatable bond is defined as a single non-ring bond attached to a nonterminal non-hydrogen atom. Hamri et al (2022) reported that a higher number of rotatable bonds in the ligand allows for more conformations and improves binding activity.…”
Section: Residues In Hydrophobic Interactionmentioning
confidence: 99%
“…Finally, it could have been due to the morphological changes in the cellulose materials, which influenced the dye’s accessibility within the micropore domains. In fact there is a semi-quantitative dependence between the level of the ECH content and the level of the discoloration [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A clear indication of compounds good drug absorption properties such bioavailability, intestinal absorption, Caco-2 permeability, and blood-brain barrier penetration (Francis and Chakraborty 2022;Ertl et al 2000). In addition, the number of rotatable bond were within the established limit of 6-170 rotatable bonds (Hamri et al 2022). A high number of rotatable bonds indicates high molecular flexibility, which acts as an indicator of a good oral bioavailability of the drugs (Veber et al 2002).…”
Section: Molecular Docking Evaluationmentioning
confidence: 99%